PERANCANGAN BUSANA WANITA TERINSPIRASI BUDAYA SENI WAYANG KULIT SEBAGAI APLIKASI - Soelistyowati, Soelistyowati (SENADA (Seminar Nasional Manajemen, Desain dan Aplikasi Bisnis Teknologi), 2019)
Clothing is the main need, especially the special needs of women who follow fashion trends, fashion is a major need in women's lives. As a creative industry, the lack of interest in making art and culture is an idea in today's creativity. Because of the lack of information and knowledge about culture for young people, this form is related to the current generation with the development of technology, to better introduce puppet art cultural ideas. Puppet is one of Indonesia's most important works that spread meaningful moral messages. Before the puppet show began, gunungan is usually displayed in various puppet games, for example in wayang purwa, wayang gedog, wayang krucil, wayang golek, wayang suluh and so on. Gunungan is a symbol of life, so that every picture in it contains many philosophical meanings, where the needs of the children of the generation must be preserved. This study is a qualitative description with literature study stages using observation and questionnaires, data collection techniques obtained from experts and exstrime user